2001
DOI: 10.1002/mc.1042
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinase‐9 in progression of mouse skin carcinogenesis

Abstract: Invasion of malignant tumor cells is required for the formation of metastatic colonies. Uncontrolled expression of matrix metalloproteinase (MMP)-2 and MMP-9 is a critical part of the invasive potential of tumor cells and is affected by the balance between the enzymes and the inhibitors secreted by the cell. Here we analyzed the expression and activity of the two gelatinases (MMP-2 and MMP-9) as well as the expression levels of the tissue inhibitor of metalloproteinase (TIMP2)-, in different stages of carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The promoter elements of GM-CSF, MMP-9 and MMP-3 bind different AP-1 complexes in a selective manner (Szabowski et al, 2000;Hulboy et al, 2001;Papathoma et al, 2001). The present study shows that TNFR1 and TNFR2 can regulate multiple c-Jun containing AP-1 complexes, since differential expression of GM-CSF, MMP-9 and MMP-3 was observed in TNFR1 À/À compared to TNFR2 À/À .…”
Section: Discussionmentioning
confidence: 99%
“…The promoter elements of GM-CSF, MMP-9 and MMP-3 bind different AP-1 complexes in a selective manner (Szabowski et al, 2000;Hulboy et al, 2001;Papathoma et al, 2001). The present study shows that TNFR1 and TNFR2 can regulate multiple c-Jun containing AP-1 complexes, since differential expression of GM-CSF, MMP-9 and MMP-3 was observed in TNFR1 À/À compared to TNFR2 À/À .…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is expressed by normal keratinocytes (Han et al, 2001;Kobayashi et al, 2001) and is induced in migrating keratinocytes following wounding in vitro (McCawley et al, 1998) and in vivo (Lund et al, 1999;Mohan et al, 2002). Transformed keratinocytes and SCC also express MMP-9 (Papathoma et al, 2001;Thomas et al, 2001a). MMP-9 has been extensively studied in many human and murine cancers due to its potential role in tumour invasion and metastasis (Naylor et al, 1994;Liabakk et al, 1996;Hanemaaijer et al, 2000;Scott et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression of MMP-9 during the progression of carcinogenesis, and decreased tumor metastasis in MMP-9-deficient mice have been reported 43,44 . These findings suggested that MMP-9 is a crucial factor for the progression of carcinogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%